Identification of a Kulshan caldera correlative tephra in the Palouse loess of Washington State, northwest USA. Issue 2 (September 2016) - King, Georgina E.; Pearce, Nicholas J.G.; Roberts, Helen M.; Smith, Victoria C.; Westgate, John A.; Gaylord, David R.; Sweeney, Mark R.
Abstract: The Kulshan caldera formed at ∼1.15 Ma on the present-day site of Mt. Baker, Washington State, northwest USA and erupted a compositionally zoned (dacite-rhyolite) magma and a correlative eruptive, the Lake Tapps tephra. This tephra has previously been described, but only from the Puget Lowland of NW Washington. Here an occurrence of a Kulshan caldera correlative tephra is described from the Quaternary Palouse loess at the Washtucna site (WA-3). Site WA-3 is located in east-central Washington, ∼340 km southeast of the Kulshan caldera and ∼300 km east-southeast of the Lake Tapps occurrence in the Puget Lowland. Major- and trace element chemistry and location of the deposit at Washtucna within reversed polarity sediments indicates that it is not correlative with the Mesa Falls, Rockland, Bishop Ash, Lava Creek B or Huckleberry Ridge tephras. Instead the Washtucna deposit is related to the Lake Tapps tephra by fractional crystallisation, but is chemically distinct, a consequence of its eruption from a compositionally zoned magma chamber. The correlation of the Washtucna occurrence to the Kulshan caldera-forming eruption indicates that it had an eruptive volume exceeding 100 km 3, and that its tephra could provide a valuable early-Pleistocene chronostratigraphic marker in the Pacific Northwest.